Transferable Vancomycin resistance in a community-associated mrsa lineagetransferable vancomycin resistance in a community-associated MRSA lineage (2014)
We report the case of a patient from Brazil with a bloodstream infection caused by a strain of methicillin-resistant Staphylococcus aureus (MRSA) that was susceptible to vancomycin (designated BR-VSSA) but that acquired the vanA gene cluster during antibiotic therapy and became resistant to vancomycin (designated BR-VRSA). Both strains belong to the sequence type (ST) 8 community-associated genetic lineage that carries the staphylococcal chromosomal cassette mec (SCCmec) type IVa and the S. aureus protein A gene (spa) type t292 and are phylogenetically related to MRSA lineage USA300. A conjugative plasmid of 55,706 bp (pBRZ01) carrying the vanA cluster was identified and readily transferred to other staphylococci. The pBRZ01 plasmid harbors DNA sequences that are typical of the plasmid-associated replication genes rep24 or rep21 described in community-associated MRSA strains from Australia (pWBG745). The presence and dissemination of community-associated MRSA containing vanA could become a serious public health concern.